Socio-spatial differences between homicide and suicide in Argentina, 1994-2014: Socio-spatial differences between homicide and suicide - Leveau, Carlos Marcelo (2022)
The objectives of this study are to discover the conformation of spatio-temporal clusters of suicides, homicides and deaths due to injuries of undetermined intention (MLIND) in Argentina, during the period 1994-2014, and to analyze the spatio-temporal association between suicide or homicide clusters and MLIND clusters in Argentina during the same period. The spatial units were the departments of Argentina. Space-time scan statistics were performed to detect clusters by sex and age groups (10-29 years, 30-59 years and 60 or more years). Two space-time models were used: multinomial and Bernoulli. The emergence of homicide clusters in men was more associated with steeper drops in employment levels, between 1991 and 2001, compared to suicide clusters. Areas with the highest population density and with the highest percentage of Unsatisfied Basic Needs (poverty indicator) were more likely to be included in clusters with high proportions of homicide in men, compared to suicide. There was a greater spatio-temporal overlap between MLIND and homicides. The results obtained support the hypotheses of (1) a geographical differentiation between homicides and suicides in times of economic crisis; and (2) MLIND would represent mostly hidden homicides.